Home » Past Questions » Mathematics » Make x the subject of the relation \(\frac{1 + ax}{1 - ax}\) = \(\frac{p}{q}\)

Make x the subject of the relation \(\frac{1 + ax}{1 - ax}\) = \(\frac{p}{q}\)


Question

Make x the subject of the relation \(\frac{1 + ax}{1 - ax}\) = \(\frac{p}{q}\)

Options

A) \(\frac{p + q}{a(p - q)}\)

B) \(\frac{p - q}{a(p + q)}\)

C) \(\frac{p - q}{apq}\)

D) \(\frac{pq}{a(p - q)}\)

The correct answer is B.

Explanation:

\(\frac{1 + ax}{1 - ax}\) = \(\frac{p}{q}\) by cross multiplication,
q(1 + ax) = p(1 - ax)
q + qax = p - pax
qax + pax = p - q
∴ x = \(\frac{p - q}{a(p + q)}\)

More Past Questions:


Dicussion (1)

  • \(\frac{1 + ax}{1 - ax}\) = \(\frac{p}{q}\) by cross multiplication,
    q(1 + ax) = p(1 - ax)
    q + qax = p - pax
    qax + pax = p - q
    ∴ x = \(\frac{p - q}{a(p + q)}\)

    Reply
    Like